CD43-independent augmentation of mouse T-cell function by glycoprotein cleaving enzymes - Berger, Scott B (Blackwell Science Inc, 2006)
Previous work has shown that the function of mouse CD4(+) T cells can be augmented by an enzyme, O-sialoglycoprotein endopeptidase (OSGE), which cleaves surface CD43, suggesting the idea that the high levels of glycosylated CD43 found on T cells from aged mice may contribute to immune senescence. New results now show that OSGE improves T-cell function even in mice lacking CD43, showing that other glycoproteins must contribute to the OSGE effect on function. Evaluation of other enzymes found two whose ability to stimulate CD4 activation was higher in aged than in young T cells. One of these, PNGase F, is a glycosidase specific for N-linked glycans, and the other, ST-Siase(2,3) from Salmonella typhimurium, is specific for α2,3-linked terminal sialic acid residues. Parallel lectin-binding experiments showed that removal of α2,3-linked sialic acid residues vulnerable to PNGase F and ST-Siase(2,3) was also greater in old than in young T cells. The preferential ability of PNGase F and ST-Siase(2,3) to improve the function of T cells from aged mice may involve cleavage of glycoproteins containing α2,3-linked sialic acid residues on N-linked or O-linked glycans or both.